Strategi Koping Orang Tua dan Dukungan Keluarga dengan Kualitas Hidup pada Anak Kanker yang Menjalani Kemoterapi - Ayu Puspita Dewi, Dyah; Wahyudi, Totok; Buyu Prakoso, Adi (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Cancer is one of the non-communicable diseases that is the leading cause of death in children worldwide and must undergo intensive treatment such as chemotherapy which has side effects of anxiety and depression that affect the child's quality of life. In this situation, family support and parental coping strategies are important factors that can help children in the process of adapting to the disease and treatment. Parents who are able to manage stress with positive coping strategies and strong family support can improve the child's psychological well-being and improve their quality of life during therapy. To determine the relationship between parental coping strategies and family support on the quality of life of children with cancer undergoing chemotherapy at Dr. Moewardi Surakarta Regional Hospital. The research method used a cross-sectional design and consecutive sampling technique on 50 respondents. Statistical results using the Spearman-Rank test showed a p-value of 0.000 (p <0.05), which indicates a significant relationship between parental coping strategies and family support on the quality of life of children with cancer undergoing chemotherapy. Parental coping strategies and family support play an important role in determining the quality of life of children with cancer. Health workers are expected to provide education and ongoing psychosocial support to families.